Challenges in Early Learning and Child Care for Quebec's English-speaking Community - Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
Early childhood education and care (ECEC). Early learning and child care. Nursery school. Preschool. Daycare. Centres de la petite enfance (CPE). There are many names and acronyms, but they all refer to the care and, ideally, educative care of young children in the years before compulsory elementary schooling. Modern wisdom views such programs as essential, and yet, in Quebec, English-speaking families face unique challenges in accessing them. This research brief explores these barriers, current efforts being made to address them, and potential solutions.

Défis en matière d'apprentissage et garde des jeunes enfants au sein de la communauté d'expression anglaise du Québec - Bell, Shannon (Quebec English-Speaking Communities Research Network (QUESCREN), 2024)
Services de garde éducatifs à l’enfance (SGEE). Éducation à la petite enfance. Maternelle. Préscolaire. Garderies. Centres de la petite enfance (CPE). Les désignations sont nombreuses, mais elles se rapportent toutes à des programmes de garde, et idéalement d’éducation, destinés aux tout-petits avant leur fréquentation obligatoire de l’école primaire. Bien que ces programmes soient aujourd’hui considérés comme essentiels, les familles anglophones du Québec se heurtent à de réels défis pour y accéder. Le présent résumé de recherche se penche sur les obstacles qu’elles rencontrent et les mesures prises ou à prendre pour éliminer ces obstacles.